Driver's Seat: Understanding Divergent Zoochorous Dispersal of Propagules - Coughlan, Neil E.; Dickey, James W. E.; Cuthbert, Ross N.; Kelly, Thomas C.; Jansen, Marcel A. K.; Dick, Jaimie T. A. (Frontiers in Ecology and Evolution, 2019)
The functional role, relative importance, and the spatial and temporal parameters of different vector species, which underpin the passive dispersal (zoochory) of organisms (or their propagules), are frequently poorly understood. Accordingly, a conceptual framework capable of providing a rigorous and unified assessment for the dispersal capacity of vector species is required. Here, we propose and apply a series of novel metrics, the Dispersal Potential (DP), the Relative Dispersal Potential (RDP), and the Combined Dispersal Potential (CDP), to predict and classify likely dispersal and vector importance. In essence, DP = Np × Tv, whereby Np is the per capita propagule load (e.g., mean, minimum, or maximum abundance) or species richness of propagules carried per individual vector species, while Tv is the total number of possible vectors (e.g., individuals of a single species at a source site, local scale abundances, or entire continental populations). Further, the ratio based metric RDP allows for DP comparison between species, while the CDP accumulates the DP of a variety of vector species. An additional Relative CDP (RCDP) metric facilitates comparison between the CDP for multiple vectors to that of one or more additional vectors. The proposed metrics can also be used to assess intraspecific differences (e.g., ontogeny). Accordingly, we examine a variety of case studies and present calculations to ascertain the usefulness of our proposed metrics. Overall, the metrics can be used to quantify and rank the prominence of different dispersers that facilitate biological connectivity. Finally, we argue that adoption of these metrics and variants thereof, will provide a more realistic measure of species' functional roles than examination of interaction intensities alone, which will enhance understanding of zoochory within and across dispersal networks.